Efficiency of Reverse Osmosis Usage in Drinking Water Depots to Reduce Iron (Fe3+), Copper (Cu2+) and Zinc (Zn2+) Ion Levels - Zul Alfian; M. Arifin Siahaan; Harry Agusnar (Talenta Publisher, 2024)
Research on the efficiency of reverse-osmosis drinking water depot to decreased levels of iron (Fe3+), Copper (Cu2+) and Zinc (Zn2+) ions have been done. The raw, the treated, and waste water are filtered using reverse osmosis (RO) three times a week. HNO3 then was added to the sample until it reached 15 mL. The determination of the concentration of the three ions was performed using atomic absorption spectrophotometer (AAS). The results showed a decrease of Fe3+ concentration of 73.21%, for Cu2+ decrease by 80.25%, while Zn2+ decrease by 82.08%. For waste water obtained iron ion concentration of 0.1794 mg/L, for Cu2+ by 0.0239 mg/L, while Zn2+ by 0.0962 mg/L.